Design of RF front-end circuit blocks for low-power applications - Lim, Kok Meng (2008)
This report aims to provide a comprehensive review as well as the design of the various high frequency circuits found in almost all the transceivers in the market today. Wireless communication has become a natural part of everyone’s life, its presence can be seen all around. The high frequency circuits include low noise amplifiers (LNA), mixers and pre-amplifiers (PA).